2016
DOI: 10.1016/j.jflm.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

“An absolutely necessary piece”: A qualitative study of legal perspectives on medical affidavits in the asylum process

Abstract: A key challenge for asylum seekers in the United States is being able to provide evidence of prior persecution in their home countries. Medical/psychological affidavits corroborating applicants’ accounts often make the difference between successful and unsuccessful applications. The purpose of this study was to identify the unmet demand for and features of effective medical/psychological affidavits in the asylum process, as well as the personal and systemic barriers for asylum seekers. This is a qualitative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…In accordance with other research (Scruggs et al., ), the results of this study highlight the need for more professionals to be trained in the forensic evaluation of asylum seekers. Our findings suggest that exposure to asylum work should begin while future mental health workers are still students in their respective academic programs, and it should include coursework not only in the mental health correlates of ill treatment and human rights violations but also in the role of legal and policy issues on this population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In accordance with other research (Scruggs et al., ), the results of this study highlight the need for more professionals to be trained in the forensic evaluation of asylum seekers. Our findings suggest that exposure to asylum work should begin while future mental health workers are still students in their respective academic programs, and it should include coursework not only in the mental health correlates of ill treatment and human rights violations but also in the role of legal and policy issues on this population.…”
Section: Discussionsupporting
confidence: 91%
“…Although their systematic review of the literature did not include perspectives of mental health clinicians, Robertshaw, Dhesi, and Jones () noted that healthcare professionals who provide services for asylum seekers face challenges due to a lack of training and a sense of isolation associated with limited support when working with trauma. Similarly, in a qualitative study of asylum lawyers, Scruggs, Guetterman, Meyer, VanArtsdalen, and Heisler () noted a shortage of practitioners who were prepared to conduct psychological evaluations for their clients.…”
mentioning
confidence: 99%
“…The overwhelming observation of the review is the significance of these partnerships to improve legal outcomes; ten out of ten articles that discussed the delivery of medical knowledge to legal cases described how people were more likely to receive positive legal outcomes when medical professionals contribute to legal proceedings [13][14][15][16][17][18][19][20][21][22]. The legitimatization of trauma and persecution through medical professionals in legal spaces may also be crucial for protecting the lives of migrants who have suffered greatly in both sending and receiving communities alike [13]. Moreover, the finding that people may feel more comfortable disclosing personal trauma and persecution to medical professionals compared to legal professionals suggests these types of partnerships are important for court proceedings as well as for building the best case for individuals seeking asylum.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we projected that more articles would focus on co-location. While co-location is optimal for patients because it means that patients do not have to travel between sites, it also creates more security for people to convey more sensitive information than may appear for legal counsel and avoids causing retraumatization without having psychiatric care on-hand [13,25]. Having mental health services in the same place as legal services also reduces stigma towards obtaining mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…A medical examination can contribute to a successful asylum claim by documenting the effects of persecution or torture. 6 One study found that asylum seekers with a medical evaluation performed by a health professional were granted asylum 89% of the time, compared with a national average rate of 37.5%. 7 This paper reviews the contributions a physician can make in performing medical forensic examinations of asylum seekers.…”
Section: Introductionmentioning
confidence: 99%